Impact of baseline characteristics and beta‐cell function on the efficacy and safety of subcutaneous once‐weekly semaglutide: A patient‐level, pooled analysis of the SUSTAIN 1‐5 trials. Issue 3 (14th November 2019) - Aroda, Vanita R.; Capehorn, Matthew S.; Chaykin, Louis; Frias, Juan P.; Lausvig, Nanna L.; Macura, Stanislava; Lüdemann, Jörg; Madsbad, Sten; Rosenstock, Julio; Tabak, Omur; Tadayon, Sayeh; Bain, Stephen C.
Abstract: Aim: To evaluate the impact of relevant patient‐level characteristics on the efficacy and safety of subcutaneous, once‐weekly semaglutide in subjects with type 2 diabetes. Materials and Methods: Exploratory post hoc analyses of pooled SUSTAIN 1‐5 (phase 3a) randomized, controlled trials examined the change from baseline in HbA1c and body weight (BW), and the proportions of subjects achieving the composite endpoint (HbA1c < 7.0% [53 mmol/mol]), without weight gain or severe/blood glucose‐confirmed symptomatic hypoglycaemia at week 30 with semaglutide (0.5/1.0 mg) across clinically relevant patient subgroups: baseline HbA1c (≤7.5%, >7.5%‐8.0%, >8.0%‐8.5%, >8.5%‐9.0% and > 9.0%), background medications, diabetes duration and pancreatic beta‐cell function. Results: Mean HbA1c (% point) reductions increased from lowest to highest HbA1c subgroups (−0.9%, −1.2%, ‐1.5%, −1.7% and −2.3% [effect of subgroup within treatment: P = 0.247] for semaglutide 0.5 mg, and −1.1%, −1.4%, −1.9%, −2.1% and −2.7% [ P = 0.045] for semaglutide 1.0 mg), with mean HbA1c ranges at week 30 of 6.3%‐7.3% and 6.1%‐6.9%, respectively. The corresponding BW reductions generally decreased with increasing baseline HbA1c (−4.4, −3.9, −3.9, −3.3 and −2.9 kg [ P = 0.004], and −6.4, −5.9, −5.2, −4.5 and −4.8 kg [ P < 0.001], respectively). HbA1c and BW reductions were consistently greater for semaglutide 1.0 mg versus 0.5 mg across background medication, diabetes duration and pancreatic beta‐cell function subgroups. Adverse events with semaglutide were consistent with the glucagon‐like peptide‐1 receptor agonist class, with gastrointestinal events the most common. Conclusions: Semaglutide was consistently efficacious across the continuum of diabetes care in a broad spectrum of patient subgroups with a range of clinical characteristics.